Evaluation of emergency contraception use among women receiving gynecological treatment in the Brazilian Amazon - Paulo Sérgio Barbalho Priante; Jaqueline Neves Lubianca; Christine Cioba; Helena von Eye Corleta; Edison Capp (Clinical and Biomedical Research, 2014)
Introduction: The use of a postcoital hormonal contraception regimen has been described and is known as emergency contraception (EC) or “the morning-after pill”. The aim of this study was to evaluate the use and level of knowledge about emergency oral contraception (EC) among women attending the gynecology outpatient clinic of the Hospital Fundação Santa Casa de Misericórdia of the State ofPará, the second largest state in the Brazilian Amazon.